Cyanobacterial small chlorophyll-binding protein ScpD (HliB) is located on the periphery of photosystem II in the vicinity of PsbH and CP47 subunits - Promnares, Kamoltip; Komenda, Josef; Bumba, Ladislav; Nebesarova, Jana; Vacha, Frantisek; Tichy, Martin (The Journal of biological chemistry, 2006)
Cyanobacteria contain several genes coding for small one-helix proteins called SCPs or HLIPs with significant sequence similarity to chlorophyll a/b-binding proteins. To localize one of these proteins, ScpD, in the cells of the cyanobacterium Synechocystis sp. PCC 6803, we constructed several mutants in which ScpD was expressed as a His-tagged protein (ScpDHis). Using two-dimensional native-SDS electrophoresis of thylakoid membranes or isolated Photosystem II (PSII), we determined that after high-light treatment most of the ScpDHis protein in a cell is associated with PSII. The ScpDHis protein was present in both monomeric and dimeric PSII core complexes and also in the core subcomplex lacking CP43. However, the association with PSII was abolished in the mutant lacking the PSII subunit PsbH. In a PSII mutant lacking cytochrome b(559), which does not accumulate PSII, ScpDHis is associated with CP47. The interaction of ScpDHis with PsbH and CP47 was further confirmed by electron microscopy of PSII labeled with Ni-NTA Nanogold. Single particle image analysis identified the location of the labeled ScpDHis at the periphery of the PSII core complex in the vicinity of the PsbH and CP47. Because of the fact that ScpDHis did not form any large structures bound to PSII and because of its accumulation in PSII subcomplexes containing CP47 and PsbH we suggest that ScpD is involved in a process of PSII assembly/repair during the turnover of pigment-binding proteins, particularly CP47.
Keywords: Synechocystis; kyselina nitrilotrioctová; nikl; Nickel; krystalografie rentgenová; mutace; Nitrilotriacetic Acid; Cyanobacteria; Bacterial Proteins; Epitopes; epitopy; imunohistochemie; Protein Subunits; sinice; Thylakoids; podjednotky proteinů; molekulární modely; Crystallography, X-Ray; Models, Molecular; Light-Harvesting Protein Complexes; tylakoidy; Immunohistochemistry; dimerizace; bakteriální proteiny; Photosystem II Protein Complex; Dimerization; Mutation; světlosběrné proteinové komplexy; Histidine; fotosystém II (proteinový komplex); histidin